Efektivitas Hendrich Fall Scale (HFS) dan Morse Fall Scale (MFS) dengan Penilaian Risiko Jatuh pada Lansia - Maita Sarah; Elyani Sembiring (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2021)
The goal of understanding fall risk in the elderly, prevention and protection is to improve clinical and care satisfaction. Another anticipatory method that can be used to predict falling conditions is the assessment of the risk of falling in the elderly. The Hendrich Fall Scale (HFS) and Morse Fall Scale (MFS) are a form of assessment to anticipate the risk of falling in the elderly in nursing homes for patients. The aim is to determine the effectiveness of the Hendrich Fall Scale and the Morse Fall Scale with an assessment of the Risk of Fall in the Elderly. The research design used in this study is a longitudinal comparative design. The total sample in this study was 40 elderly. This research was conducted at the Nursing Home Foundation Guna Budi Bakti Medan Labuhan. Data collection using the Hendrich Fall Scale and Morse Fall Scale. Data analysis using Chi Square. Fall risk assessment using the Hendrich Fall Scale (HFS), elderly people with a high risk of falling (25.0%), moderate risk of falling (65.0%). Fall risk assessment used the Morse Fall Scale (MFS), the elderly who had a high risk of falling (39.1%), moderate risk of falling (47.8%). It is recommended that seniors at risk of falling should be assessed using the MFS instrument.